The importance of neurotechnology-based teaching in education (MMIT Proceedings, 2024)
This article provides information on the importance of neural networks in education. Neural networks are one of the most interesting technologies of our time. Trained to work with incredible amounts of data and uses this knowledge to solve complex problems in demanding industries. Interest in neural networks is growing every year, and the possibilities they offer are becoming more and more impressive.